Development of the Recommended Summary Plan for eEmergency Care and Treatment (ReSPECT). (1st March 2020) - Hawkes, Claire A.; Fritz, Zoe; Deas, Gavin; Ahmedzai, Sam H.; Richardson, Alison; Pitcher, David; Spiller, Juliet; Perkins, Gavin D.; ,
Abstract: Introduction: Do-not-attempt-cardiopulmonary-resuscitation (DNACPR) practice has been shown to be variable and sub-optimal. This paper describes the development of the Recommended Summary Plan for Emergency Care and Treatment (ReSPECT). ReSPECT is a process which encourages shared understanding of a patient's condition and what outcomes they value and fear, before recording clinical recommendations about cardiopulmonary-resuscitation (CPR) within a broader plan for emergency care and treatment. Methods: ReSPECT was developed iteratively, with integral stakeholder engagement, informed by the Knowledge-to-Action cycle. Mixed methods included: synthesis of existing literature; a national online consultation exercise; cognitive interviews with users; a patient-public involvement (PPI) workshop and a usability pilot, to ensure acceptability by both patients and professionals. Results: The majority (89%) of consultation respondents supported the concept of emergency care and treatment plans. Key features identified in the evaluation and incorporated into ReSPECT were: The importance of discussions between patient and clinician to inform realistic treatment preferences and clarity in the resulting recommendations recorded by the clinician on the form. The process is compliant with UK mental capacity laws. Documentation should be recognised across all health and care settings. There should be opportunity for timely review based on individual need. Conclusion: ReSPECT is designed to facilitate discussions about a person's preferences to inform emergency care and treatment plans (including CPR) for use across all health and care settings. It has been developed iteratively with a range of stakeholders. Further research will be needed to assess the influence of ReSPECT on patient-centred decisions, experience and health outcomes.